2021
DOI: 10.37341/interest.v0i0.298
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness Of Video And E-Booklet Media In Health Education On Improving The Knowledge Of Pregnant Women About The Pregnancy Danger Signs At Jetis 1 Public Health Center Of Bantul Regency

Abstract: Background: Danger signs of pregnancy before causing complications can be detected early independently through learning media such as videos and e-booklets. The purpose of this study was to determine the effectiveness of video and e-booklet media in improving the knowledge of pregnant women about the danger signs of pregnancy Methods: This study was conducted in December 2020-January 2021 at Jetis 1 Public Health Center, Bantul Regency and used the type of quasi-experimental research and pretest-posttest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Video media containing sight and hearing senses will be easier to understand. They can increase the knowledge of pregnant women compared to e-booklets that only have a sense of sight (Widuri et al, 2021). The results of this study also stated an increase in motivation for implementing pregnancy exercises in the leaflet intervention group (p=0.026).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Video media containing sight and hearing senses will be easier to understand. They can increase the knowledge of pregnant women compared to e-booklets that only have a sense of sight (Widuri et al, 2021). The results of this study also stated an increase in motivation for implementing pregnancy exercises in the leaflet intervention group (p=0.026).…”
Section: Discussionmentioning
confidence: 54%
“…This is similar to a study that stated that both media increased the knowledge of pregnant women with a p-value of 0.000 for videos and a p-value of 0.000 for e-booklets. It was also found that videos were more effective than e-booklets in increasing the knowledge of pregnant women (p-value 0.031) (Widuri et al, 2021). The knowledge gained will affect pregnant women's motivation toward their pregnancy exercises (Yulianti & Halimatussaadiah, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Hal tersebut menunjukkan bahwa penggunaan media video efektif dalam meningkatkan pengetahuan ibu hamil dibandingkan dengan kelompok yang tidak diberikan video. Penelitian yang dilaksanakan oleh (Herinawati et al, 2021) menyatakan bahwa penggunaan video meningkatkan efektivitas efikasi diri dalam memahami tanda-tanda bahaya kehamilan dibandingkan dengan buku KIA [10].…”
Section: Metode Penelitianunclassified
“…Hasil penelitian ini secara statistik terdapat perbedaan yang signifikan pengetahuan responden sebelum dan setelah diberikan pendidikan kesehatan menggunakan video. Menurut Widuri et al, (2021) pendidikan kesehatan merupakan proses pembelajaran terencana dan dinamis untuk memodifikasi perilaku melalui peningkatan keterampilan, pengetahuan maupun perubahan sikap yang berkaitan dengan perbaikan pola hidup ke arah yang lebih sehat dan diaplikasikan pada skala individu hingga masyarakat serta pada penerapan program kesehatan. Pendidikan kesehatan juga memiliki peran penting dalam menunjang program.…”
Section: Analisa Bivariat Gambaran Pengetahuan Sebelum Dan Setelah Di...unclassified